Survival Strategy During the Covid-19 Pandemic: Research on the Sustainability of MSMEs - Dekeng Setyo Budiarto; An Nisa Prita Savira (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
E-commerce is a popular business solution for most people to increase income and maintain business sustainability during this Covid-19 pandemic. This study aims to determine the effect of e-commerce and financial literacy on the performance and sustainability of MSMEs. This study uses primary data by distributing questionnaires to 160 MSMEs owners in Gunungkidul Regencies. The sampling method used is purposive sampling with specific criteria. The hypothesis test used is SEM-PLS. This study is a development of several previous studies using a linear regression model. In contrast, this study uses a structural model because this method can detect more complicated models. The results of hypothesis testing indicate that e-commerce and financial literacy affect performance, and performance affects business sustainability. The results of this study can provide ideas to MSMEs owners to improve their financial literacy skills and use e-commerce to survive in an uncertain environmental situation. In addition, support from the government is needed in the form of an infrastructure network so that MSMEs access is more accessible.